Bioresorbable scaffolds in peripheral arterial disease. (April 2014) - Kassimis, George; Spiliopoulos, Stavros; Katsanos, Konstantinos; Tsetis, Dimitrios; Krokidis, Miltiadis E
<x xml:space="preserve">Abstract</x> The risk of in-stent restenosis has been dramatically reduced with the use of thin-strut nitinol and balloon-expandable drug-eluting stents in the peripheral arterial territory. However, the presence of a permanent endovascular device is linked to a series of events that can lead to restenosis and stent thrombosis. Significant advances in the technology of bioresorbable materials have delivered the potential for fully bioresorbable scaffolds (BRS), which are able to mechanically support the artery wall and elute an anti-restenotic drug for a predetermined time period after which the scaffold becomes fully absorbed into the vascular wall. Currently, several vascular BRS are available, undergoing evaluation either in clinical trials or in preclinical settings. The aim of this review is to present the new developments in BRS technology, describe the mechanisms involved in the resorption process, and discuss the current and potential future prospects of this innovative treatment option for peripheral arterial disease.